Defect and Material Mechanics Proceedings of the International Symposium on Defect and Material Mechanics (ISDMM), held in Aussois, France, March 25–29, 2007 - Dascalu, C.; Maugin, Gérard A.; Stolz, Claude; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
This volume presents recent developments in the theory of defects and the mechanics of material forces. Most of the contributions were presented at the International Symposium on Defect and Material Forces (ISDMM2007), held in Aussois, France, March 25-29, 2007. The mechanics of material forces, originated in the works of Eshelby, provide a rational framework for the description of driving forces on evolving inhomogeneities and structural changes in continua. The general eshelbian mechanics formulation comes up with a unifying treatment of different phenomena like fracture and damage evolution, phase transitions, plasticity and dislocation motion, etc. The articles concern both theoretical and computational aspects of the material mechanics of defects. Among the addressed topics are fracture and damage, electromagnetoelasticity, plasticity, distributed dislocations, thermodynamics, poroelasticity, generalized continua, structural optimization, conservation laws and symmetries, multiscale approaches, and numerical solution strategies. This is a hardbound spin-off reprinted from The International Journal of Fracture 147:1-4.
Preface -- Reciprocity in fracture and defect mechanics -- Configurational forces and gauge conditions in electromagnetic bodies -- The anti-symmetry principle for quasi-static crack propagation in Mode III -- Configurational balance and entropy sinks -- Application of invariant integrals to the problems of defect identification -- On application of classical Eshelby approach to calculating effective elastic moduli of dispersed composites -- Material forces in finite elasto-plasticity with continuously distributed dislocations -- Distributed dislocation approach for cracks in couple-stress elasticity: shear modes -- Bifurcation of equilibrium solutions and defects nucleation -- Theoretical and numerical aspects of the material and spatial settings in nonlinear electro-elastostatics -- Energy-based r-adaptivity: a solution strategy and applications to fracture mechanics -- Variational design sensitivity analysis in the context of structural optimization and configurational mechanics -- An anisotropic elastic formulation for configurational forces in stress space -- Conservation laws, duality and symmetry loss in solid mechanics -- Phase field simulation of domain structures in ferroelectric materials within the context of inhomogeneity evolution -- An adaptive singular finite element in nonlinear fracture mechanics -- Moving singularities in thermoelastic solids -- Dislocation tri-material solution in the analysis of bridged crack in anisotropic bimaterial half-space -- Study of the simple extension tear test sample for rubber with Configurational Mechanics -- Stress-driven diffusion in a deforming and evolving elastic circular tube of single component solid with vacancies -- Mode II intersonic crack propagation in poroelastic media -- Material forces for crack analysis of functionally graded materials in adaptively refined FE-meshes -- A multiscale approach to damage configurational forces.
Keywords: Mechanical engineering; Mechanics; Mechanics, Applied; Applied mathematics; Engineering mathematics; Computational complexity; Mechanical Engineering; Theoretical and Applied Mechanics; Solid Mechanics; Mathematical and Computational Engineering; Complexity; Solid Mechanics